Comparative Efficacy of Droplet Digital PCR and Real-time PCR for In-house Validation of Porcine Detection and Quantification Protocol: An Approach towards Artificial Recombinant Plasmid - Nuraeni, Umi; Astuti, Retno Tri; Malau, Jekmal; Dewantoro, Auraga; Apriori, Dini; Lusiana, Evellin Dewi; Prasetya, Bambang (Science and Technology: Recent Updates and Future Prospects Vol. 11, 2024)
This research will contribute to the development of an external standard for qPCR-based quantification and a routine inspection protocol for instrument performance and kit and interlaboratory-user capabilities in national-wide inspections. Authenticity and traceability are essential for modern food and medicine inspection, and reliable techniques are important for the trade of halal foods, which reach more than 20 percent of the world market. Porcine ingredients can be a potential source of food adulteration when fraudulently added to processed foods without proper labeling. A sensitive and accurate porcine detection method is required to develop a conformity assessment system that includes laboratory testing for porcine-free certification. This study proposes a procedure that could be incorporated into the development of a standardized control and protocol for real-time PCR (qPCR) methods and their traceability using droplet digital PCR (ddPCR). The design used a recombinant pUC57 plasmid as an amplification target to carry the 97 bp fragment of the porcine ATCB gene. The absolute quantification and linearity assessment showed high precision with R2 values of 0.9971 and 0.9998 for qPCR and ddPCR, respectively. In general, both methods showed comparable results in terms of linearity and detection limit. Beta-actin and other single-copy genes are less effective than mitochondrial DNA (mtDNA) for assessing the authentication of porcine testing, possibly because mtDNA is abundant in cells, thereby increasing its amplification probability. However, both limits of detection assessments showed high sensitivity, although ddPCR showed a slightly higher sensitivity than that of qPCR, especially at low DNA concentrations. Evaluations of multiple-sample and inter-participatory testing demonstrated the qPCR method's excellent sensitivity, wide application, and robustness. Consequently, we draw the conclusion that the digital PCR approach yielded more reliable results based on a low quantity (less than five copy number) recombinant plasmid study. These findings may offer scientific data that regulatory bodies, particularly those in Indonesia, can use to build and formulate a reliable qPCR procedure for porcine detection that makes use of predicted DNA quantities.